Analyzing the Effectiveness of the READi System in Helping Non-Native English-Speaking Preschoolers in Sarawak Learn the Alphabet : A Pilot Study - Tan, Yen Vee; Julia Ai Cheng, Lee; Rehman Ullah, Khan; Chen, Chwen Jen; Kartini, Abd Ghani; Sarah Flora, Samson Juan; Brian Loh, Chung Shiong (The University of Southern Mississippi, 2025)
In Sarawak, Malaysia, many children come from multicultural backgrounds and are predominantly non-native English speakers, making preschool education essential for developing early literacy skills in English. However, high teacher-child ratios can impede effective learning. The READi system, a module-based multisensory web-based early literacy intervention, was introduced as a supplementary classroom tool to address this challenge. This pilot study specifically evaluated the effectiveness of the “Alphabet Adventure” module within the READi system on enhancing alphabet knowledge, with a focus on letter recognition and letter name knowledge. The research design employed a pretest-posttest control group approach grounded in the positivist paradigm. Participants were selected through teacher referrals and paired based on their pretest performance to ensure comparable baselines before being randomly assigned to either the experimental or control group. Data analyses were conducted using the Wilcoxon Signed Rank and Mann-Whitney U tests. The results indicated that the READi system significantly improved uppercase letter recognition among children. These findings offer valuable insights into future adaptations of the READi system, aimed at better addressing children’s educational challenges and improving teaching practices.